Implementation of reinforcement learning architecture to augment an AI that can self-learn to play video games - Mahmud, Aqil; Khan, Aswat Karim; Hasan Rafi, Mohammad Mehdi; Fahim, Kazi Rayhan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.